2020
DOI: 10.1017/jfm.2020.826
|View full text |Cite
|
Sign up to set email alerts
|

Thermal convection over fractal surfaces

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 68 publications
(192 reference statements)
2
20
0
Order By: Relevance
“…2001; Goluskin & Doering 2016; Toppaladoddi et al. 2020). In these situations, the systems are in a statistical steady state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2001; Goluskin & Doering 2016; Toppaladoddi et al. 2020). In these situations, the systems are in a statistical steady state.…”
Section: Resultsmentioning
confidence: 99%
“…In non-rotating turbulent Rayleigh-Bénard convection, with Dirichlet boundary conditions and periodically rough boundaries, Toppaladoddi, Succi & Wettlaufer (2015 showed that, for a given roughness wavelength, there is a ratio of the thermal boundary layer thickness to the roughness amplitude that optimizes Nu. Moreover, this enhancement of heat transport is a general consequence of roughness, observed for a wide range of geometries from rough on all surfaces to fractal boundaries (Roche et al 2001;Goluskin & Doering 2016;Toppaladoddi et al 2020). In these situations, the systems are in a statistical steady state.…”
Section: Maximal Phase Boundary Roughness and Maximal Heat Fluxmentioning
confidence: 95%
“…Secondly, the lower boundary in the CBL is neither smooth, nor uniformly heated. Recent results show that neither nonuniform heating (Bakhuis et al, 2018) nor rough boundaries (Zhu et al, 2019;Toppaladoddi et al, 2021) drastically change the dynamics of RBC, though the latter does tend to increase the heat flux towards the so-called "ultimate regime", equivalent to the free-convective regime which dominates discussion of scaling in the atmospheric convective boundary layer.…”
Section: The Relevance Of Rbc To Atmospheric Flowsmentioning
confidence: 99%
“…Secondly, the lower boundary in the CBL is neither smooth, nor uniformly heated. Recent results show that neither non‐uniform heating (Bakhuis et al ., 2018) nor rough boundaries (Zhu et al ., 2019; Toppaladoddi et al ., 2021) drastically change the dynamics of RBC, though the latter does tend to increase the heat flux towards the so‐called “ultimate regime”, equivalent to the free‐convective regime which dominates discussion of scaling in the atmospheric convective boundary layer.…”
Section: Rayleigh–bénard Convection (Rbc)mentioning
confidence: 99%